Granting Leave to Patients in Bavarian Forensic-Psychiatric Hospitals: A Survey to Describe the Current Process and Develop Guidelines - Sklenarova, Halina; Neutze, Janina; Kretschmer, Thomas; Nitschke, Joachim (Frontiers in Psychiatry, 2020)
Forensic-psychiatric patients reoffending or absconding during the leave granted to them (hereafter referred to as “granted leave”) have gained increased attention by researchers and the general public. The patients’ right to freedom on the one hand and the need for protection of the general public from serious harm on the other hand represent broadly discussed ethical issues. Thus, demands on quality regarding decisions on patients’ granted leaves might be high. Despite such requirements, research on decision-making processes regarding granting leave in forensic psychiatry is very limited and focuses primarily on particular aspects. The present study aims at providing a first overview of the decision-making processes regarding granted leave in forensic psychiatry as a whole. Furthermore, the link between the particular steps of the process and absconding should be explored. In this way, the study results should contribute to provide a theoretical framework for the development of guidelines concerning granted leave in forensic psychiatry. A combination of qualitative and quantitative approaches will be used to collect data: information about risk assessment, decisions on granted leave, and documentation systems in forensic psychiatry will be collected via semi-structured interviews and quantified for further analyses using a checklist developed for this study; data on the implementation of risk assessment tools and documented patient information will be obtained via two self-constructed questionnaires; information about the absolute number of abscondences per hospital will be obtained from the Bavarian Authority for Forensic Commitment. The sample will include staff from all 13 forensic-psychiatric hospitals in Bavaria (Germany) comprising six professional groups: hospital directors, security officers, complementary therapists, psychiatrists, psychologists, social workers, and nursing staff. In each hospital, at least one member of each professional group should participate in the study. In total, 151 interviews will be held. As the study goals are descriptive, there are no pre-formulated hypotheses. Developing guidelines would be the first step towards further standardization of the granted leave decisional process in forensic psychiatry and to make it more transparent for patients, staff members, hospital directors, and the government.